EVALUASI KEBIJAKAN PERDA KOTA PALU NO. 3 TAHUN 2018 (Studi Kasus Penanganan Gelandangan/Pengemis Anak dan Perempuan di Kota Palu) - Muthia (Pusat Studi Gender dan Anak, IAIN Palu, 2021)
The rapid urban development is the goal of many regions in Indonesia. However, urban development often creates new problems, including homeless and children/women beggars. A number of tactical steps have been carried out by the government in reducing the number of homeless and child/women beggars in Indonesia. One of them is through a normative approach, which is regional regulations, as applied in Palu, Central Sulawesi by issuing Regional Regulation No. 3 of 2018 on the management of homeless people and children/women beggars. However, these efforts have not yet reduced the number of homeless and beggars for children/women. This article aims to identify the effectiveness of Palu Regulation No. 3 of 2018 in dealing with the problem of homeless people and children/women beggars. By applying the implementation-style analysis of Grindle to evaluate Regional Regulation (Perda) No.3 of 2018, this research applied a comparative literature study data collection method from secondary data that the researchers had collected, including periodic reports from the Palu City Government and related agencies. In addition, data were also obtained from the results of field observation. Some points that were observed in this study were in front of the office of Regional People's Representative Assembly (DPRD) of Palu. The results showed that he implementation of Palu Regional Regulation No. 3 of 2018 as seen from the policy content had been optimized.